Spatial farming systems diversity and micronutrient intakes of rural children in Ethiopia - Moges, Tibebu; Brouwer, Inge D.; Delbiso, Tefera Darge; Remans, Roseline; Baudron, Frédéric; Belachew, Tefera; Groot, Jeroen C.J. (Wiley, 2022)
Own production contributes much of the food supply in smallholder production sys-tems in low- and middle-income countries like Ethiopia. Understanding the potentialas well as constraints of these production systems in terms of nutrient supplies isthus a critical step to design interventions to improve nutrient intakes. The objectivesof this study were (1) to assess the usual total intakes of vitamin A, iron and zincamong rural children and (2) to investigate whether the intakes these nutrients areassociated with differences in the dominant farming systems between spatial clus-ters. Using nationally representative intake data of 4,902 children 6–35 months ofage, usual intake and the proportion of inadequate intakes of vitamin A, iron and zincwere calculated. A multi-level model was used to examine the association betweenindividual-level and cluster-level variables with the usual total dietary intakes of thesenutrients. The diet was dominated by starchy foods. Consumption of animal sourcefoods, vitamin A-rich fruits and vegetables was low. We found a high prevalence ofinadequate intake of vitamin A and zinc (85.4% and 49.5%, respectively). Relatively,low prevalence of inadequate intake of iron (8.4%) was reported. The spatial farmingsystems diversity across the rural clusters explained 48.2%, 57.2% and 26.7% of theobserved variation in the usual total dietary intakes of vitamin A, iron and zinc,respectively. Our findings indicated the importance of farming system diversity at thelandscape level as one of the determinant factors for individual usual total dietaryintakes of vitamin A, iron and zinc.